Inventarisasi Potensi Daya Saing Spasial Lahan Rawa Lebak untukPengembangan Pertanian di Sumatera Selatan - Waluyo Waluyo; Alkasuma Alkasuma; Susilawati Susilawati; Suparwoto Suparwoto (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Waluyo, Alkasuma, Susilawati, Suparwoto. 2012Â Spatial Inventory of Potential Competitiveness Swamp Land for Agricultural Development in South Sumatra. J. Lahan Suboptimal 1(1):64-71.Â Swampy marsh land has great competitive advantage for farmland development.The purposes of this study were 1)to identify the spread of potential swampy marsh land for food crops in major production centers; 2)to understand thecontent, quantity,and distribution of minerals essential for health in the low lands of South Sumatra. Data were collected through some surveys using transects (toposequen), including delineation of maps, flooding/ground water, state of the microrelief, soilbase material, land use, and land surface condition. Ground observations were based on the Soil Survey Manual. The results indicated that Sungai Pinang and Rantau Panjang has three types of swampy land, namely shallow swampy marsh, mid marsh low lands, and swamps in the low lands. Swampy marsh as the potential competitiveness for its antioxidant mineral deposit (Fe, Mn, Cu, Zn, and Se) can produce good functional food products such as Padi seputih, Pelita Rampak, Ketan Sinde, Padi Petek. These varieties have considerably high antioxidant mineral. Therefore, the use of swampyland must be directed. Shallow and intermediate wetlands can be used for rice, pulses and vegetables whereas deep wetlands are suitable for fishing.